An Intravenous 100-mL Lipid Emulsion Infusion Dramatically Improves Myocardial Glucose Metabolism Extinction in Cardiac FDG PET Clinical Practice. (June 2021) - Dietz, Matthieu; Paulmier, Benoît; Berthier, Frédéric; Civaia, Filippo; Mocquot, François; Serrano, Benjamin; Nataf, Valérie; Hugonnet, Florent; Faraggi, Marc
Abstract : Purpose: Physiological myocardial accumulation of FDG impairs the diagnosis of inflammatory/infectious or tumoral myocardial detection by FDG PET/CT. We prospectively evaluated the addition, 3 hours before imaging, of an intravenous 100-mL lipid emulsion infusion (Intralipid) to a high-fat, low-carbohydrate diet (HFLCD) for at least 2 meals followed by a fast of at least 6 to 12 hours in patients referred for the diagnosis of myocardial inflammation, endocarditis, cardiac or paracardiac masses, intracardiac device, or prosthetic valve infections. Methods: Data of 58 patients consecutively included (28 Intralipid patients, 30 controls with HFLCD alone) were compared. FDG uptake in normal myocardium was scored from 0 (complete myocardial suppression) to 3 (high diffuse uptake). Myocardial maximal, peak, and mean SUV and the rate of interpretable images according to the clinical indication were measured. Results: Compared with controls, Intralipid infusion significantly improved the rate of score 0 (89% vs 63%, P = 0.021), of interpretable images according to the clinical indication (100% vs 72%, P = 0.0047) and decreased all myocardial SUV values (eg, SUVmax median, 1.9 [interquartile range, 1.7–2.5] vs 3.1 [interquartile range, 2.3–4.1]; P < 0.001). Conclusions: A lipid emulsion infusion in addition to HFLCD better suppresses cardiac glucose metabolism than HFLCD alone.